Pendidikan Kesehatan Hipertensi dan Cek Kesehatan di Dusun Tambalan, Pleret, Bantul, Yogyakarta - Murwani, Arita; Sari, Fatimah; Julia K, Juda (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2023)
Hypertension is one of the major health problems in the world that must be addressed immediately, according to data from the World Health Organization, hypertension attacks hypertension in women (40.17%) higher than men (34.83 percent), the highest hypertension in Yogyakarta is in Gunung Kidul (39.25%), the second is Kulon Progo (34.70%), the third is Sleman (32.01%), the fourth is Bantul (29.89%). primary and secondary prevention strategies aimed at reducing the incidence of morbidity, mortality, as well as reducing the incidence of hypertension Primary health services in the community are the spearhead in controlling hypertension. If implemented properly, it can reduce morbidity, complications and death due to hypertension. The purpose of this activity is to increase public knowledge in order to avoid hypertension which triggers the emergence of certain accompanying diseases. The method of carrying out activities is by conducting direct exposure through PPT. The number of participants in this activity amounted to 72 people including the elderly (elderly), and teenagers, cadres of the Puskesmas in Tambalan Pleret Hamlet, Bantul Yogyakarta. The implementation of this activity is through lectures using PPT media so that it is easy to convey to parents and teenagers who are present at TPA Ar-Rahmat Dusun Tambalan Pleret Bantul Yogyakarta. The activity went smoothly as seen from the enthusiasm of the participants who attended. Participants' knowledge and understanding of hypertension was better than before the counseling.